MECHANISM OF INTEGRATING INSURANCE COMPANIES AND BANKS IN THE SYSTEM OF FINANCE MARKET PATICIPANTS' INTERACTION - Oleg D. Averchenko (Вестник Российского экономического университета имени Г. В. Плеханова, 2017)
Russian finance market is characterized by prevailing of banks' work over non-bank finance institutions, including insurance companies. It does not allow the latter to realize their investment functions in full and impedes formation of customer confidence to finance market. That is why working out of mechanism of integrating insurance companies with banks could become a basis for further development of Russian finance market. The author through methods of analysis, logical generalization, scientific abstraction, as well as system-structural analysis designed a mechanism of integrating insurance companies and banks. The place of insurance companies and banks' integration was found. Instruments to manage integration were proposed.